Análise numérica em laje de concreto armado em uma direção - influência da taxa de armadura longitudinal na resistência à força cortante - Silva, Silvio Quirino da (2022)
The literature addresses some factors that influence the shear strength, such as the compressive strength of concrete, the longitudinal reinforcement rate, the height of the element section and others. Focusing on solid slabs of reinforced concrete in one direction and without transverse reinforcement subjected to shear force, this work aims to perform a numerical analysis of the behavior of this element, verifying the influence that the rate of longitudinal reinforcement exerts on the gain of resistance to shear force. Therefore, it was necessary to use experimental data to assess the numerical model, that is, to obtain a model representative of the experimental one. Considering these aspects, simulations were performed with variation of the factors already exposed that affect the resistance to shear force. In this way, the force x displacement curves, the shear stresses and the cracking panorama of the slabs were obtained. In addition to this numerical analysis performed using the ANSYS® Workbench program, a statistical analysis of Factorial Experimental Design with Analysis of Variance was applied using the Minitab® program, verifying which factor most significantly affected the shear stress, the response variable extracted from the numerical simulation and considering a significance level of 5%. The results showed that the steel rate of the longitudinal reinforcement influenced the obtaining of the ultimate force and displacement, however, the factor that most impacted the shear stress was the height of the slab. In addition, when the height interacts with the compressive strength of the concrete, it obtains a better yield in the resistant capacity of this element, however, it is important to remember that the longitudinal reinforcement rate had its contribution in the transfer of shear stresses, being a factor which also affects shear strength, but not predominantly. The cracking panorama, on the other hand, begins in the region of application of the displacement with diagonal directions, consequently presenting the section of the slab that is in Stages I, II and III, at the moment of its rupture. Finally, it was possible to determine that the height of the cross section of the slab was the relevant factor, in relation to the others, being this parameter responsible for the greatest influence or contribution in the gain of resistance in the complementary mechanisms. On the other hand, the ripening at the upper edge of the slab was a less relevant factor, which proved not to be useful in the resistance capacity of this element.